Activity and safety of crizotinib in patients with alveolar soft part sarcoma with rearrangement of TFE3: European Organization for Research and Treatment of Cancer (EORTC) phase II trial 90101 ‘CREATE’ - Schöffski, Patrick; Kasper, Bernd (Annals of oncology, 2018)
Background - Alveolar soft part sarcoma (ASPS) is an orphan malignancy associated with a rearrangement of transcription factor E3 (TFE3), leading to abnormal MET gene expression. We prospectively assessed the efficacy and safety of the MET tyrosine kinase inhibitor crizotinib in patients with advanced or metastatic ASPS. - Patients and methods - Eligible patients with reference pathology-confirmed ASPS received oral crizotinib 250mg bd. By assessing the presence or absence of a TFE3 rearrangement, patients were attributed to MET+and MET− sub-cohorts. The primary end point was the objective response rate (ORR) according to local investigator. Secondary end points included duration of response, disease control rate (DCR), progression-free survival (PFS), progression-free rate, overall survival (OS) and safety. - Results - Among 53 consenting patients, all had a centrally confirmed ASPS and 48 were treated. A total of 45 were eligible, treated and assessable. Among 40 MET+patients, 1 achieved a confirmed partial response (PR) that lasted 215days and 35 had stable disease (SD) as best response (ORR: 2.5%, 95% CI 0.6% to 80.6%). Further efficacy end points in MET+cases were DCR: 90.0% (95% CI 76.3% to 97.2%), 1-year PFS rate: 37.5% (95% CI 22.9% to 52.1%) and 1-year OS rate: 97.4% (95% CI 82.8% to 99.6%). Among 4 MET− patients, 1 achieved a PR that lasted 801days and 3 had SD (ORR: 25.0%, 95% CI 0.6% to 80.6%) for a DCR of 100% (95% CI 39.8% to 100.0%). The 1-year PFS rate in MET− cases was 50% (95% CI 5.8% to 84.5%) and the 1-year OS rate was 75% (95% CI 12.8% to 96.1%). One patient with unknown MET status due to technical failure achieved SD but stopped treatment due to progression after 17 cycles. The most common crizotinib-related adverse events were nausea [34/48 (70.8%)], vomiting [22/48 (45.8%)], blurred vision [22/48 (45.8%)], diarrhoea (20/48 (41.7%)] and fatigue [19/48 (39.6%)]. - Conclusion - According to European Organization for Research and Treatment of Cancer (EORTC) efficacy criteria for soft tissue sarcoma, our study demonstrated that crizotinib has activity in TFE3 rearranged ASPS MET+patients. - Clinical trial number - EORTC 90101, NCT01524926